A theoretical analysis of an air stripper–biofilter system (ASBF) for industrial wastewater treatment - Shareefdeen, Zarook (2017)
In this study, we focus on the industrial wastewater contaminated with volatile organic compounds (or VOC’s) which are carbon-containing compounds such as benzene, toluene, xylene, styrene, etc. VOC’s in general are toxic and potentially carcinogenic and they harm aquatic life and the environment. In this research, we focus on a theoretical analysis of VOC removal from industrial wastewater using a hybrid system that combines two processes, namely air-stripping and biofiltration (ASBF). In this system, airstream is first contacted with industrial wastewater in an air-stripping tower and depending on the air stripping efficiency clean water, which is devoid of VOCs, leaves the unit as the effluent. The contaminated air stream is then fed to a biofilter that eliminates VOCs by biological degradation. The theoretical predictions conducted through modeling demonstrate effective removal of VOCs from wastewater can be achieved in the ASBF system under current operating conditions.